"Keep Working for Environmental Justice No Matter How Bleak Things Look. Don't Give Up. Don't Just Go Away": An Interview With Wilma Subra. (November 2018) - Sullivan, John; Parady, Katelyn
MacArthur prize-winning community scientist, Wilma Subra participated in the research of the Gulf Coast Health Alliance: Health Risks Related to the Macondo Spill project. Ms. Subra chronicles the arc of her career as a public health advocate who has informed communities nationwide of active and potential health risks. She has been most active in the U.S. Gulf Coast region where oil production infrastructure, petrochemical refining and production plants, and hazardous waste storage and treatment facilities seem as common as live oaks and red fish. A pioneer in the growing field of do-it-yourself citizen science, Ms. Subra shares her views on community engagement, community-based participatory research, and effective risk communication and also explains how citizen scientists were an essential component in the response to the Deep Water Horizon oil rig explosion and spill.